Invariância de escala temporal em equações intensidade-duração-frequência (IDF) da região metropolitana de Belo Horizonte - Guilherme Soares Almeida Rodrigues (2020)
Several cities in the world face problems related to excess or scarcity of water. In rainy periods, cities and their inhabitants are subject to flooding and landslides. For the dimensioning of a hydraulic work the design flow can be known through direct measurements, obtained in fluviometric stations. However, in the urban context the basins are generally not monitored. The absence of data leads to he estimation of the design flow indirectly, through rain-flow models. The study of extreme rainfall is carried out through the analysis of rainfall intensity, its duration and the frequency with which this extreme rainfall occurs. To facilitate the analysis, it is common to develop equations that model the Intensity-Duration-Frequency of rains, known as IDF relations. IDF relationships can be developed for a specific location or region. In this paper, we carried out expansions in series of maximum annual intensities in order to increase the size of the series and use the time-scale invariance methodology of IDF relations to estimate the IDF curve of the Belo Horizonte Metropolitan Region. Scaling factors were obtained for each station and a regional scaling factor was modeled. The probability distribution was obtained with the aid of SEAF software, which uses fuzzy logic to recommend probability distributions. A regional IDF equation was obtained as a result that depends only on daily data of maximum daily annual intensity. The results obtained by the regional IDF ratio generated in the work were compared to the observed data and the IDF in force in the region.